2022
DOI: 10.14202/vetworld.2022.2315-2322
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effects of oak bark (Quercus robur) and heather herb (Calluna vulgaris L.) extracts against the causative bacteria of bovine mastitis

Abstract: Background and Aim: Bovine mastitis has a negative impact on animals, and improper antibiotic use has caused an increase in bacterial resistance. Therefore, medicinal plants could serve as an alternative treatment for this condition. Polyphenols have potential as antibiotic agents. Oak bark has long been used as a medicine and has shown antibacterial effects. Moreover, research on heather plant demonstrated that it has antibacterial properties. This study aimed to assess the antibacterial effects of oak (Querc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Previous studies have reported the pharmacological and therapeutic benefits of forest tree extracts in animals and humans, notably including the extracts of English oak and related species of the Quercus genus [24,25,26]. In complement, our findings suggest the potential of such extracts as antibacterial phytosanitary agents in crop protection, similar to Cibele et al [27] reporting the antibacterial activity of aqueous extracts from twelve Brazilian medicinal plants against the plant pathogens Acidovorax citrulli , Pectobacterium carotovorum subsp.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported the pharmacological and therapeutic benefits of forest tree extracts in animals and humans, notably including the extracts of English oak and related species of the Quercus genus [24,25,26]. In complement, our findings suggest the potential of such extracts as antibacterial phytosanitary agents in crop protection, similar to Cibele et al [27] reporting the antibacterial activity of aqueous extracts from twelve Brazilian medicinal plants against the plant pathogens Acidovorax citrulli , Pectobacterium carotovorum subsp.…”
Section: Resultsmentioning
confidence: 99%
“…Extracts from the flowers of T. vulgare minimally inhibited the growth of S. agalactiae, but extracts from the leaves had minimal effects against S. uberis and Serratia liquefaciens. When the same bacterial isolates of bovine mastitis were tested, 70% acetone extracts of Quercus robur bark and 30% ethanol extracts of Calluna vulgaris herb had broader antibacterial spectra and lower MIC and MBC [48]. One study reported that Serratia liquefaciens was sensitive to ethanolic extracts of Mentha pulegium, Nepeta cataria, Melissa officinalis, Agastache foeniculum, Lavandula angustifolia, Origanum vulgare, Althaea officinalis, Plantago lanceolata, Artemisia absinthium, Populus nigra, and Evernia prunastri, all of which contain both essential oil and phenolic compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Šukele et al presents results on using different extrahents on oak bark. They report acetone and 30% ethanol having the best outcome in terms of using these extracts for growth control of Streptococcus agalactiae , Streptococcus uberis , Serratia liquefaciens , and Staphylococcus aureus [ 18 ]. In a 2018 article Valencia-Aviles et al report that hot water extracts were more effective that using 90% ethanol for both phenols and antioxidants [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oak bark extracts were also shown to work in treating periodontal disease [ 17 ]. Additionally, multiple studies reported that oak bark derivatives were demonstrated to have antibacterial properties [ 13 , 18 , 19 , 20 ]. Similarly, as with oak leaves, oak bark derivatives were reported to positively affect digestion in the rumen [ 21 ].…”
Section: Introductionmentioning
confidence: 99%